Curcumin Modulates miR‐19/PTEN/AKT/p53 Axis to Suppress Bisphenol A‐induced MCF‐7 Breast Cancer Cell Proliferation. (15th May 2014) - Li, Xiaoting; Xie, Wei; Xie, Chunfeng; Huang, Cong; Zhu, Jianyun; Liang, Zhaofeng; Deng, Feifei; Zhu, Mingming; Zhu, Weiwei; Wu, Rui; Wu, Jieshu; Geng, Shanshan; et al.
<x xml:space="preserve">Abstract</x> Breast cancer is the most common cancer in women. Bisphenol A (BPA), as a known endocrine disrupter, is closely related to the development of breast cancer. Curcumin has been clinically used in chemopreventation and treatment of cancer; however, it remains unknown whether microRNAs are involved in curcumin‐mediated protection from BPA‐associated promotive effects on breast cancer. In the present study, we showed that BPA exhibited estrogenic activity by increasing the proliferation of estrogen‐receptor‐positive MCF‐7 human breast cancer cells and triggering transition of the cells from G1 to S phase. Curcumin inhibited the proliferative effects of BPA on MCF‐7 cells. Meanwhile, BPA‐induced upregulation of oncogenic miR‐19a and miR‐19b, and the dysregulated expression of miR‐19‐related downstream proteins, including PTEN, p‐AKT, p‐MDM2, p53, and proliferating cell nuclear antigen, were reversed by curcumin. Furthermore, the important role of miR‐19 in BPA‐mediated MCF‐7 cell proliferation was also illustrated. These results suggest for the first time that curcumin modulates miR‐19/PTEN/AKT/p53 axis to exhibit its protective effects against BPA‐associated breast cancer promotion. Findings from this study could provide new insights into the molecular mechanisms by which BPA exerts its breast‐cancer‐promoting effect as well as its target intervention. Copyright © 2014 John Wiley & Sons, Ltd.